Future market changes for Malaysian dental therapists: a qualitative study amongst dental therapists in the east of peninsular Malaysia on their career motivation and expectations - Mohd Ramle, Nur Syazwani; Ahmad Sabri, Siti Zulaiha; Cheong, Joo Ming; Ab Murat, Norintan; Che Musa, Muhd Firdaus (2020)
Introduction: The dental workforce in most countries is facing unprecedented changes. Malaysia has responded by approving the legislation for the registration of dental therapists under the Dental Act 2018. Aim: To identify the potential market changes of future dental professionals in Malaysia from the perspectives of dental therapists in East Peninsular Malaysia on their career motivation and expectations. Material and methods: Dental therapists from two dental organisations in East Malaysia were invited to participate in an audiotaped semi-structured interview (n=26); using a pre-tested topic guide. The qualitative data was transcribed and analysed using a Framework Analysis. Results: Dental therapists have moderate to high perception of knowledge and awareness with the provision of the Dental Act 2018. The expansion of the working sector and patients’ age-group has changed their short and long-term career expectation; mainly professional goals, working pattern and sector (public or private). Furthermore, the respondents’ perceptions are influenced by financial factor and work-life balance. Nevertheless, the Malaysian dental therapists share the same career motivations as the dentists. Conclusion: Dental therapist’ views on their career motivation and expectations broadly mirror their dentist counterpart and dental therapists in other countries. Their implications for the future, including possible uncertainties, particularly in regards to the privatization of the workforce were identified; and the tension of balancing practitioners/public health needs with their professional career expectations. This research highlights the influence of dynamic changes in market policy regarding workforce mobility and the importance of flexible strategies for the training, recruitment and retention of dental therapists.